BH3-mimetic small molecule inhibits the growth and recurrence of adenoid cystic carcinoma. Issue 9 (September 2015) - Acasigua, Gerson A.; Warner, Kristy A.; Nör, Felipe; Helman, Joseph; Pearson, Alexander T.; Fossati, Anna C.; Wang, Shaomeng; Nör, Jacques E.
<x xml:space="preserve">Abstract</x> Highlights BM-1197 is a new, potent, BH3 mimetics small molecule inhibitor of Bcl-2/Bcl-xL BM-1197 potently induces caspase-3 and apoptosis of adenoid cystic carcinoma cells. BM-1197 slows down tumor growth in PDX models of adenoid cystic carcinoma. BM-1197 prevents local recurrence of PDX tumors. These data unveil therapeutic potential of BH3-mimetics in adenoid cystic carcinoma.